Actions for Gender Balance in Informatics Across Europe (Springer Nature, 2025)
This book is a open access. The primary purpose of this book is to serve as a comprehensive guide, translating research into best practices to promote gender inclusivity in informatics. The handbook seeks to empower its readers, providing them with actionable recommendations to bridge the gender gap in informatics. This initiative aims to have an immediate impact on the informatics community, raising awareness and interest through its practical resources, and on the society bringing more women into computer science and technological studies and following career steps. This book provides you with five years of research on gender equity and improving the gender balance in Informatics across Europe. It translates current research on gender inclusivity into practical strategies and intervention methods. It offers recommendations for the recruitment, retention, and promotion of female computer scientists at different academic and industrial levels, and insights into fostering mutually beneficial cooperation between universities and industries. We have collected data from different target audiences and different education and career levels to provide insights into why we have low girl and women participation rates in sciences, why we have a leaky pipeline in academia, and why women leave the industry. We have analyzed this data and identified four target audiences for activities and policy influence. We provide sets of recommendations for each of these target groups on how to become active in advocacy as well as specific actions in their daily environments to improve learning and work environments as well as retention of women students and personnel. We provide ample scenarios of how to apply our findings in practice and share materials both in the book as well as in free public access online documentation to further disseminate and make use of this knowledge. The book serves as joint European voice of Informatics to increase the equity for women in the field.